Unique Features Of Painting In The Professional Training Of Fine Art Teachers (Eurasian Journal of Learning and Academic Teaching, 2022)
The article analyzes the theoretical ideas and considerations, as well as the practical application of graphics, which is a type of art, and the uniqueness of the role of a pen in painting